2014
DOI: 10.1007/s00414-014-1002-4
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion assessment in the location of facial landmarks on photographs

Abstract: The morphological assessment of facial features using photographs has played an important role in forensic anthropology. The analysis of anthropometric landmarks for determining facial dimensions and angles has been considered in diverse forensic areas. Hence, the quantification of the error associated to the location of facial landmarks seems to be necessary when photographs become a key element of the forensic procedure. In this work, we statistically evaluate the inter- and intra-observer dispersions relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 17 publications
6
41
7
Order By: Relevance
“…As has already been explained in this article, placing landmarks on a photograph is a difficult task that presents a particular degree of imprecision [18], [19]. Thus, the imprecision in the location of landmarks has a negative effect on the final SFO achieved (best transformation).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As has already been explained in this article, placing landmarks on a photograph is a difficult task that presents a particular degree of imprecision [18], [19]. Thus, the imprecision in the location of landmarks has a negative effect on the final SFO achieved (best transformation).…”
Section: Discussionmentioning
confidence: 90%
“…The uncertainty related to the location of facial landmarks refers to the difficult task of placing landmarks on a photograph [18], [19]. Among other reasons, the definition of many anthropometric landmarks is imprecise in nature.…”
Section: Modeling the Uncertainty Related To The Location Of Faciamentioning
confidence: 99%
See 1 more Smart Citation
“…Although we can find these obscure landmarks on the surfaces of 3D facial images, we cannot identify them exactly without palpation. Previous studies [22,23] showed that there were comparatively large errors in the positioning of some landmarks such as (se), (zy), and (go) in photo anthropometry.…”
Section: Discussionmentioning
confidence: 99%
“…The works developed by authors such as [10,11,12,13,14] serve as examples of how computer algorithms can automate SFO and accommodate the uncertainty/fuzziness of some facial landmarks [15] and of the soft tissues [16,17]. These methods represent a clear step forward since they have managed to reduce time and subjectivity inherent to manual approaches.…”
Section: Introductionmentioning
confidence: 99%